2015
DOI: 10.5539/ijef.v7n8p182
|View full text |Cite
|
Sign up to set email alerts
|

Bankruptcy Prediction Using Support Vector Machines and Feature Selection During the Recent Financial Crisis

Abstract: This study aims at identifying an optimal set of features for predicting firms bankruptcy events in the current macroeconomic context. To this aim, among many financial features, we propose new country-specific factors which consider the macroeconomic conditions of the countries where firms operate. Our forecasting model is based on Support Vector Machines (SVMs), which are tools employed in supervised learning. Firstly, starting from a wide set of variables commonly used for bankruptcy prediction we assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Härdle et al (2009) reported on exploring the suitability of smooth support vector machines to examine the important factors on influencing the precision of prediction. Dellepiane et al (2015) propose new country-specific factors using SVM as the forecasting model and assess the general effectiveness of SVMs by comparing it with the performances of other commonly used methods.…”
Section: Chinese Firm Predictionmentioning
confidence: 99%
“…Härdle et al (2009) reported on exploring the suitability of smooth support vector machines to examine the important factors on influencing the precision of prediction. Dellepiane et al (2015) propose new country-specific factors using SVM as the forecasting model and assess the general effectiveness of SVMs by comparing it with the performances of other commonly used methods.…”
Section: Chinese Firm Predictionmentioning
confidence: 99%
“…In the last decade, SVM approach has been widely applied in insolvency prediction to improve the performance [19,23,26,30,31,32]. In general, the numerical results demonstrate that SVM outperforms neural networks and statistical methods in predicting financial failures [9]. However, a kernel function is always necessary for the nonlinearly separable data sets in the classical SVM model [25].…”
mentioning
confidence: 99%
“…Note that feature selection aims to find a subset of input features which performs as well as all available features. Several researchers have noticed this problem and proposed some algorithms for searching optimal subsets of predictors [9,11]. Finally, we conduct some numerical experiments based on the real data of non-life insurers from USA to show the predictive power and efficiency of our proposed method compared with other benchmark methods.…”
mentioning
confidence: 99%
See 2 more Smart Citations